In search of the skilled city: Skills and the occupational evolution of British cities. (January 2020) - Sunley, Peter; Martin, Ron; Gardiner, Ben; Pike, Andy
Recent research has argued that human capital has become the key driver of city growth and that there is a widening divergence between high- and low-skill cities. This skilled-city view includes several stylised propositions. The first is that more skills and human capital generate stronger economic growth; the second is that already-skilled cities are becoming ever more skilled; and, the third is that larger cities tend to have stronger concentrations of, and faster growth in, high-skilled, cognitive occupations. Using a detailed data set for occupational change in 85 urban Travel to Work Areas in Britain between 1981 and 2015, this paper evaluates whether these propositions apply to British urban evolution, and how they relate to the 'hollowing-out' of medium-skilled jobs. The results confirm the close interactive relationship between growth and high-skilled occupations. However, some of the skilled-city propositions, such as 'smart cities becoming smarter', and a positive relationship between agglomeration and high-skilled employment growth, do not apply in Britain where other factors have been more important. The pattern of high-skill growth has shown a strong regional dimension, and the 'emergence' of newer smaller cities, particularly in southern England, has been more evident than the 'resurgence' of large core and industrial cities.